Analysis of the impact of the pandemic on the mental health of medical professionals on the frontline in the fight against COVID-19 (Research, Society and Development, 2022)
The pandemic, social isolation, the large number of deaths caused by the coronavirus and fear affected the mental health of the Brazilian population and, specifically, of the medical class that works on the front line to combat COVID-19. This is because they deal with death full time and are at high risk of acquiring the disease due to: exposure to infected patients, self-demand, physical and mental exhaustion. The objective was to analyze the impacts of the pandemic on the mental health of medical professionals working on the front lines of the fight against COVID-19. Descriptive-exploratory and cross-sectional research, through an electronic questionnaire, on the analysis of the impact of the pandemic on the mental health of medical professionals who act as a front line in the fight against COVID-19. In view of the analysis of the field research and relating it to the bibliographic references, it became evident that of the 10 interviewees, 2 of them say that it is difficult and exhausting to deal with the death of patients with COVID-19. results, none of the professionals sought psychological care or started drug therapy for mental health disorders. In this context, it is clear that the pandemic had a relevant impact on the quality of life and work of these doctors, but no signs of a serious impact on the mental health of respondents were found, which was initially expected.